Analysis and design of blast-resistant structures - Yang, Guichang (2008)
The response of reinforced concrete beams and plates with an attached external layer of FRP platekheet on the tension face and subjected to air-blast loading are investigated using a simplified analytical model. The model comprises a number of distinct elastic phases, of which each phase terminates due to failure at a cross-section, and finally the plastic phase, when the reinforced concrete structure becomes a free movable mechanism.